The Influence of Mongol Invasion in the Kamakura Period on the Recession of the Kamakura Shogunate (Asian Journal of Social Science Studies, 2022)
This paper takes the two attempted invasions by the Yuan Dynasty (Mongol) during the Kamakura period as an example to analyze the influence of the invasion on the Kamakura Shogunate and the contradictions between the two sides. In the history of Mongol invasion of Japan, although the Kamakura Shogunate won in the war, it turned out to recession, the author wanted to explore the causes of its decline through the research and was interested in the Mongolia strikes may lead to Kamakura Shogunate recession this view, taking this opportunity to seek the Mongol strikes cause deterioration of the Kamakura Shogunate regime. At present, there are many studies on the war process in the academic circle, but there are still insufficient studies on the relationship between the Mongol attack and the decline of the Kamakura Shogunate. Therefore, this paper has certain research value. The influence of Mongol attack on the decline of Kamakura Shogunate was analyzed by reference and Internet. This paper first sorts out the background of the Mongol attack, and then briefly describes the process of the Mongol attack, namely the Bunei War and the Koan War. Finally, the influence of Mongol invasion on the collapse of Kamakura Shogunate is discussed from both political and economic aspects.